2016
DOI: 10.1109/access.2016.2569537
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Hybrid Taguchi-Genetic Algorithm for Multi-Criteria Optimization of Shaft Alignment in Marine Vessels

Abstract: An intelligent hybrid Taguchi-genetic algorithm (IHTGA) is used to optimize bearing offsets and shaft alignment in a marine vessel propulsion system. The objectives are to minimize normal shaft stress and shear force. The constraints are permissible reaction force, bearing stress, shear force, and bending moment in the shaft thrust flange under cold and hot operating conditions. Accurate alignment of the shaft for a main propulsion system is important for ensuring the safe operation of a vessel. To obtain a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…For the parameter optimization problems of the complex nonlinear functions with continuous variables, it has been shown that the HTGA method can obtain improved results regarding robustness than existing approaches. 27,34 Thus, the HTGA method is used here to design the optimal NOFBreduced-order observers. The details regarding the HTGA can be found in Ho et al 27,34 The following evolutionary environments of the HTGA are used in this section: the population size is 30, the crossover rate is 0.95, the mutation rate is 0.01, and the maximum generation is 100.…”
Section: Illustrative Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the parameter optimization problems of the complex nonlinear functions with continuous variables, it has been shown that the HTGA method can obtain improved results regarding robustness than existing approaches. 27,34 Thus, the HTGA method is used here to design the optimal NOFBreduced-order observers. The details regarding the HTGA can be found in Ho et al 27,34 The following evolutionary environments of the HTGA are used in this section: the population size is 30, the crossover rate is 0.95, the mutation rate is 0.01, and the maximum generation is 100.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…27,34 Thus, the HTGA method is used here to design the optimal NOFBreduced-order observers. The details regarding the HTGA can be found in Ho et al 27,34 The following evolutionary environments of the HTGA are used in this section: the population size is 30, the crossover rate is 0.95, the mutation rate is 0.01, and the maximum generation is 100. The type of OF considered in this section is the shifted Chebyshev series.…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…The GA is adopted in this paper to deal with the complex problem of searching for the optimal observer gain matrix in the algebraic form of (24) subject to the constraint of there being a matrix such that the LMI in (13) holds, where 24is a complex nonlinear function having continuous variables. In addition, for the parameter optimization problems of complex nonlinear functions having continuous variables, it has been shown that the Hybrid Taguchi-Genetic Algorithm (HTGA) method can obtain better results than existing approaches [47]. The HTGA method is therefore employed in this paper to design the optimal observer for a time-delay system.…”
Section: Optimal Design Of the Observer Gain Matrixmentioning
confidence: 99%
“…Step (HTGA method execution [47]). By integrating (19), (21), and (22), the HTGA method is utilized to search for the optimal observer gain matrix , where a penalty on the fitness value is given for the chromosome violating the LMI-based constraint in (13).…”
Section: Optimal Observer Design Proceduresmentioning
confidence: 99%
“…This algorithm has been applied to so many different electric motor design problems up to date [3][4][5]. In addition, the more strong algorithms constructed by combining the different artificial intelligence algorithms or other methods with genetic algorithm have been used [6][7][8][9]. The designs of permanent magnet synchronous motors are more complex and non-linear engineering problems and also contain some fuzzy facts such as other electric motor designs [10,11].…”
Section: Introductionmentioning
confidence: 99%